On the Asymptotic Behavior of Solutions to the Vlasov–Poisson System. (30th July 2021) - Ionescu, Alexandru D; Pausader, Benoit; Wang, Xuecheng; Widmayer, Klaus
Abstract: We prove small data modified scattering for the Vlasov–Poisson system in dimension d=3, using a method inspired from dispersive analysis. In particular, we identify a simple asymptotic dynamics related to the scattering mass.